HUBUNGAN ANTARA KOMUNIKASI TERAPEUTIK BIDAN DENGAN TINGKAT KEPUASAN IBU BERSALIN DALAM ASUHAN PERSALINAN NORMAL DI RSUD KRATON KABUPATEN PEKALONGAN - Diah Atmarina Yuliani Yuliani (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2021)
This therapeutic communication aims to reduce the burden of feelings and fears that exist in the patient, reduce the patients doubts and can affect other people, the environment and himself. This study aims to determine the description of maternal satisfaction, to identify the realtinship between the midwifes therapeutic communication and the level of satisfaction of the mother in childbirth care. The research design used a descriptive correlation design. The population in this study were all mothers who gave birth normally at the Kraton Hospital, Pekalongan regency. Determination of the sample using total sampling. Data anlysis using Spearmen’s rho test. Based on bivariate anylisi with Spearman rank statistical test, it was obtained a significance value (r) which was 0.0001 compared to =0.05, so r ( 0,001 < 0,05 ) so that Ho was rejected, which means that there is a relationship between the midwifes therapeutic communication with the mothers level of satisfaction giving birth in normal delivery care at the Kraton Hospotal pekalongan Regency. Based on the results of the study, maternity mothers pay more attention to information or advice given by midwives and improve good relations with health workers. For midwives to further improve therapeutic communication skills so that the provision of information can be accepted by patients and their families and further im prove the quality of delivery services.